Emerging debt and equity markets: an exploratory investigation of integration using daily data - Mandeep S. Chahal; Michael J. Rebello; Stephen D. Smith (Federal Reserve Bank of Atlanta, 1996)
In this paper we examine integration between emerging and U.S. debt and equity markets. We first investigate price changes around significant "events," in this case changes in short-term U.S. interest rates brought about by actions of the Federal Reserve. Second, we estimate the predictability of returns using both domestic and U.S. variables. Finally, we test whether a single latent variable can explain these returns. The evidence suggests that the degree of integration varies with security types and the country of origin. However, these differences between security types become less apparent over time.
Keywords: 330; Financial markets; International finance